TEKNIK TOKEN ECONOMIC UNTUK MEREDUKSI PERILAKU SELF STIMULATION PADA ANAK AUTIS DI PLAY GROUP/TAMAN KANAK-KANAK - Nyoman Suwidiani, Ni (Jurnal Pendidikan Khusus, 2016)
Abstract Some autism children often showed self stimulation behavior such as flapping hands which was continuously done so that it disturbed the learning process and the children’s daily life. The purpose of this research was to prove whether there was influence of using token economic technique toward self stimulation behavior to autism children in Mentari School kindergarten Sidoarjo or not.                 This research was experiment with Single Subject Research (SSR) of A-B design. The subject was one of the autism children in Mentari School kindergarten Sidoarjo who usually did self stimulation behavior i.e. flapping hands behavior. The research result indicated that the average self stimulation behavior was done in 30 minutes to baseline phase (A) was 21-25 times with the total duration 65-112 seconds, and to intervention phase (B) was 10-14 times with the total duration 40-52 seconds for 30 minutes.According to the data analysis, it was concluded that token economic technique could reduce self stimulation behavior (flapping hands) to autism children which was previously done 21-25 times with the total duration 65-112 seconds and then it reduced i.e. 10-14 times with the total duration 40-52 seconds in 30 minutes   Keywords: Token economic technique, self stimulation behavior